Lithic utility and risk: Examining mid to late Holocene stone points from Australia with a utility model. (October 2021) - Maloney, Tim Ryan; Hiscock, Peter
Abstract: Archaeological evidence of technology reflects myriad influences on past life, including economic contexts and mobility, which remain at the forefront of archaeological science. Given that forager groups needed to anticipate future technological needs and often had to transport tools, provisioning was necessary to enhance foraging success. Scheduling of production ensures suitable tools were available, maintained, and transported to where they were needed. This study investigates these fundamentals of interpreting past technological organisation via a critical examination of transport utility measures detected amongst bifacial points of late Holocene Australia. By focussing on one widely adopted model of these utility measures, we offer a new perspective on quantifying tool provisioning and interpreting forager mobility. These bifacial points were systematically geared to produce small and light specimens with low utility. Thus, foragers employed a strategy that sacrificed the benefits of extended utility in risky economic contexts. In return, they benefitted from having small points capable of being hafted to composite tools, enhanced the performance of those composite tools, and were light enough to permit multiple composite tools to be carried across the mid to late Holocene landscape of north Western Australia. Highlights: A return to the theoretical contrast between realised and potential utility of stone tools. Stone points of Holocene Australia formed one element of a mobile toolkit. Foraging strategy that sacrificed benefits of extended utility in risky Holocene contexts.